Robotic head and neck surgery: history, technical evolution and the future - Garas,G; Arora,A (ORL, 2018)
The first application of robotic technology in surgery was described in 1985 when a robot was used to define the trajectory for a stereotactic brain biopsy. Following its successful application in a variety of surgical operations, the da Vinci® robot, the most widely used surgical robot at present, made its clinical debut in otorhinolaryngology and head and neck surgery in 2005 when the first transoral robotic surgery (TORS) resections of base of tongue neoplasms were reported. Subsequently, the indications for TORS rapidly expanded, and they now include tumours of the oropharynx, hypopharynx, parapharyngeal space, and supraglottic larynx, as well as obstructive sleep apnoea (OSA). The da Vinci® robot has also been successfully used for scarless-in-the-neck thyroidectomy and parathyroidectomy. At present, the main barrier to the wider uptake of robotic surgery is the prohibitive cost of the da Vinci® robotic system. Several novel, flexible surgical robots are currently being developed that are likely to not only enhance patient safety and expand current indications but also drive down costs, thus making this innovation more widely available. Future directions relate to overlay technology through augmented reality/AR that allows real-time image-guidance, miniaturisation (nanorobots), and the development of autonomous robots.